The Language of Peace: Communicating to Create Harmony, Author: Rebecca Oxford, Publisher: Information Age Publishing, 2013, ISBN: 978-1-62396-094-0, Pages: 364 - Ryan, Stephen (Studies in Second Language Learning and Teaching, 2014)
Book review